MODEL PENDIDIKAN INKLUSIF UNTUK SISWA TUNANETRA - Supena., Asep (Pendidikan Luar Biasa, 2012)
Abstract; This is a summary of a comprehensive study through library and empirical research on conducting inclusive education for students with visual impairment (tunanetra). The Objective of the study is to develop an ideal model of conducting inclusive education for students with visual impairment. The study was conducted through qualitative  approach. the data was collected from observations and focus group discussions with teachers and principals in special schools and regular schools in Jakarta and Bandung. The model consists of thirteen dimentions of conducting the inclusive education that include (1) model of enrollment, (2) identification and assessment, (3) curriculum, (4) learning process, (5) classroom management, (6) human resources, (7) facilities and equipment, (8) lesson plan, (9) learning resources, (10) supporting system, (11) evaluation, (12) school management, and (13) financial.